Enchanting sites: places and folkloric figures in nineteenth-century England - Huxley, A (2024)

(untitled)
Industrialisation threatened the relationship between folklore and place. The construction of factories and railway lines transformed the scenery in which many folktales were set, while rural communities that had passed down folktales for generations dispersed to the growing cities for work. New transport infrastructure, as it moved people and print around the country with unprecedented efficiency, seemed to promote a shared national culture over a variety of local folk traditions. In the nineteenth century, the belief that folklore was disappearing from industrialising countries—widely articulated in both literary and ephemeral texts—became one of the foundational assumptions of folklore studies and the emerging disciplines of anthropology and sociology. In 1917, Max Weber famously described the fate of his times as the ‘disenchantment of the world’. This thesis contributes to a recent body of scholarship that complicates the Weberian narrative by showing how industrialisation created new opportunities for enchantment. It traces the ways in which canonical poets and novelists developed the folklore of three geographies in the context of infrastructural expansion: Tintagel Castle, Kensington Gardens, and the Thames. At the same time, it recovers forgotten works of nineteenth-century travel writing and local history to analyse not just the content of folklore but the experience of folklore. While I take a conceptual cue from Michael Saler’s argument that readers use ironic modes of thought to participate in fantasy-fiction worlds, I ask how people engage with material that is less straightforwardly fictional. Victorians often adopted playful and self-aware patterns of thought to read folklore into place, allowing them to experience enchantment without committing to belief or disbelief in the fantastic. Their daydreams revealed that folklore had serious uses in nineteenth-century England: as a tool to form attachments to place, and, crucially, to respond to environmental disaster.